Electronic structure and magnetic properties of few-layer Cr2Ge2Te6: the key role of nonlocal electron–electron interaction effects. (5th September 2019) - Menichetti, Guido; Calandra, Matteo; Polini, Marco
Abstract: Atomically-thin magnetic crystals have been recently isolated experimentally, greatly expanding the family of two-dimensional materials. In this Article we present an extensive comparative analysis of the electronic and magnetic properties of, based on density functional theory (DFT). We first show that the often-used approaches fail in predicting the ground-state properties of this material in both its monolayer and bilayer forms, and even more spectacularly in its bulk form. In the latter case, the fundamental gap decreases by increasing the Hubbard- U parameter, eventually leading to a metallic ground state for physically relevant values of U, in stark contrast with experimental data. On the contrary, the use of hybrid functionals, which naturally take into account nonlocal exchange interactions between all orbitals, yields good account of the electronic gap as measured by ARPES. We then calculate all the relevant exchange couplings (and the magneto-crystalline anisotropy energy) for monolayer, bilayer, and bulk with a hybrid functional, with super-cells containing up to 270 atoms, commenting on existing calculations with much smaller super-cell sizes. In the case of bilayer, we show that two distinct intra-layer second-neighbor exchange couplings emerge, a result which, to the best of our knowledge, has not been noticed in the literature.